2019
DOI: 10.1038/s41467-019-13022-7
|View full text |Cite
|
Sign up to set email alerts
|

Unassisted solar lignin valorisation using a compartmented photo-electro-biochemical cell

Abstract: Lignin is a major component of lignocellulosic biomass. Although it is highly recalcitrant to break down, it is a very abundant natural source of valuable aromatic carbons. Thus, the effective valorisation of lignin is crucial for realising a sustainable biorefinery chain. Here, we report a compartmented photo-electro-biochemical system for unassisted, selective, and stable lignin valorisation, in which a TiO2 photocatalyst, an atomically dispersed Co-based electrocatalyst, and a biocatalyst (lignin peroxidase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(52 citation statements)
references
References 58 publications
0
45
0
Order By: Relevance
“…The integration of electro(photo)chemical generation of H 2 O 2 system with enzymatic catalysis is known to improve the process efficiency. Lignin peroxidase has also been used for depolymerization of β-O-4 lignin model compound and lignin in a three-compartment cell separated with Nafion and cellulose membranes together with TiO 2 photocatalyst and Co-N/CNT as an electrocatalyst ( Figure 1 ) [ 54 ]. This photoelectrobiochemical system enabled lignin dimer cleavage with high conversion efficiency (93.7%) and selectivity (98.7%) to 3,4-dimethylbenzaldehyde.…”
Section: Untargeted Approach/electrocatalytic Conversion Of Ligninmentioning
confidence: 99%
“…The integration of electro(photo)chemical generation of H 2 O 2 system with enzymatic catalysis is known to improve the process efficiency. Lignin peroxidase has also been used for depolymerization of β-O-4 lignin model compound and lignin in a three-compartment cell separated with Nafion and cellulose membranes together with TiO 2 photocatalyst and Co-N/CNT as an electrocatalyst ( Figure 1 ) [ 54 ]. This photoelectrobiochemical system enabled lignin dimer cleavage with high conversion efficiency (93.7%) and selectivity (98.7%) to 3,4-dimethylbenzaldehyde.…”
Section: Untargeted Approach/electrocatalytic Conversion Of Ligninmentioning
confidence: 99%
“…Furthermore, the photo-electrobiochemical design is catalyzed the lignin depolymerization with a 98.7% selectivity and polymerization with a 73.3% yield using a lignin monomer: coniferyl alcohol. 59 In other side, the metal free organocatalytic approach for photocatalytic depolymerization of lignin monomer was developed. In this method N-phenylpheno-thiazine (PhPTH) was identified as a photocatalyst for the valorization of β-O-4 linkages in lignin monomer under irradiation of violet or Kessil LED's offered the aromatic monomers in high yields.…”
Section: Photocatalytic Oxidation Of Lignin Motifsmentioning
confidence: 99%
“…In the literature, oxygen evaluation or hydrogen evolution, followed by their utilization for organic transformation, is of current interest. ,, Along this line, after successful application of our designed Bi 2 WO 6 @DNA-2 as photoanodes in PEC water splitting, for the first time, an idea with the real-life application of the produced hydrogen is tested for feedstock conversion. For this study, the large-scale conversion of feedstock materials to value-added chemicals by photocatalytic hydrogenation/hydrogenolysis reaction is demonstrated under external hydrogen pressure.…”
Section: Catalytic Hydrogenation/hydrogenolysis Of Feedstock Model Co...mentioning
confidence: 99%
“…There were no reports to carry both PEC water splitting and feedstock conversion using the same catalyst in the literature. Ko et al recently reported the photoelectro-biochemical feedstock conversion with lignin model compound . They have studied in-situ-generated H 2 O 2 from a three-compartment photoelectro-biochemical reactor for stable and selective lignin valorization .…”
Section: Introductionmentioning
confidence: 99%